Risk of developing checkpoint immune pneumonitis and its effect on overall survival in non-small cell lung cancer patients previously treated with radiotherapy (2020)
Introduction:Immune checkpoint inhibitor-related pneumonitis (ICIP) is a potentially lifethreatening immune-related adverse event (irAE), especially in non-small cell lung cancer(NSCLC) patients. Currently, the potential for increased irAE in patients who receiveradiotherapy is scarcely known, although a connection between antitumor immuneresponses and irAEs has been suggested. In this study, we evaluated the developmentof ICIP in non-small cell lung cancer patients with prior radiotherapy, treated withimmunotherapy in the second-line.Methods:In this retrospective trial, we included patients treated with second-lineimmunotherapy at the National Cancer Institute in Mexico City from February 2015 toFebruary 2018. Clinical, radiological and treatment variables were evaluated accordingto the presence of ICIP as defined by the Common Terminology Criteria for AdverseEvents (4.0) in patients with or without a previous (≥months) history of radiotherapy.Results:Among 101 NSCLC patients who received treatment with ICIs, 22 patients(21.8%) were diagnosed with ICIP, of which 73% (16/22) had a history of radiotherapy(OR 6.04, 95% CI 2.03−18.0,p<0.001). Median progression free survival and overallsurvival were similar in patients who developed ICIP compared with those who did not,however, patients who presented grade≥2 ICIP had an increased risk of mortality (HR2.54, 95% CI 1.20−5.34,p= 0.014).Conclusion:In this real-world cohort of NSCLC patients treated with ICI, the historyof prior radiotherapy was associated with increased risk for ICIP development. Unlikeother irAEs, grade≥2 ICIP is an independent prognostic factor for decreased survivalin NSCLC patients.